STUDY OF SLANG IN EBES NGALAM COLUMN OF MALANG POST - ISFATIN K., EMY RAHMAWATI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Rahmawati, Emy. 2014. A  Study on Slang Used in Ebes Ngalam Column of Malang Post Newspaper.  Study Program of English, University of Brawijaya. Supervisor: Eni Maharsi; Co-supervisor: Muhammad Rozin. Keywords: Slang,  Ebes Ngalam  Column, Linguistic forms,  Characteristics and Function of slang   The main use of language is for communication. In society, there are language varieties used by certain groups of community. One of the  varieties  is slang. Ebes Ngalam Column of Malang Post uses the slang as one of the language varieties inside the community. This study is aimed to analize the linguistic forms of the slang used in Ebes Ngalam column and also to  identify  the characteristics and the functions of the slang.   Qualitative approach and document analysis are  employed in this study since the source of data is the word in newspaper column. The data are the slang words  produced by the columnist  under  the pseudo names  Ebes  and Kana  that contain slang. The data were taken from September 2013 issues.   This study reveals that the  linguistic forms of the slang are  found in the column are; pure back reversal, semi back reversal, phonological change, term of address, reduplication and coinage.  Meanwhile,  characteristics  of Malangnese slang are creative and fresh. As the characteristics of flippant and onomatopoeic are not found since there is no word adapted from the sound in nature, and also the Malangnese slang is the language of refinement. In addition, it has been found that the function or the reason for the use of slang by Ebes Ngalam column  is  to entertain or amuse a superior public,  to ease  social intercourse, to intimate or to prove that one belongs or has belonged to a certain community.   Finally, the result of the study  is expected to provide some useful inputs which are valuable for some students that are interested in Sociolinguistics. As for the next researcher who wishes to conduct a research on slangs, they can consider investigating contrastive slangs.